Design of Robust Power System Stabilizer in an Interconnected Power System with Wind Power Penetrations - Cuk Supriyadi; I. Ngamroo; None Sarjiya; None Tumiran; Y. Mitani (My University, 2010)
In the recent years, renewable electrical energy such as wind power generations, have achieved a significant level of penetration in the power systems due to infinite availability and low impact to environment. However, wind power generation is intermittent in nature. Matching the supply and the demand is often a problem. The power output fluctuations from wind power generations cause a problem of low frequency oscillation, deteriorate the system stability and make the power system operation more difficult. The power frequency and the tie-line power deviations persist for a long duration. In these situations, the governor system may no longer be able to absorb the frequency fluctuations due to its slow response (Elgerd & Fosha, 1970). To stabilize power oscillation, PSS is often used as an effective device to enhance the damping of electromechanical oscillations in power systems. The power system stabilizer is a supplementary control system, which is often applied as part of excitation control system. The basic function of the PSS is to apply a signal to the excitation system, creating electrical torques to the rotor, in phase with speed variation, that damp out power oscillations. In the past decades, the utilization of supplementary excitation control signals for improving the dynamic stability of power systems has received much attention. Extensive research has been conducted in many fields such as the effect of PSS on power system stability, PSS input signals, PSS optimum locations, and PSS tuning techniques. In (deMello & Concordia, 1969), the concept of synchronous machine stability as affected by excitation control has been examined. This work developed insights into effects of excitation systems and requirement of supplementary stabilizing action for such systems based on the concept of damping and synchronizing torques. These stabilizing requirements included the adjustment of voltage regulator gain parameters as well as the PSS parameters. Since the primary function of the PSS is to add damping to the power oscillations, basic control theories have been applied to select the most suitable input signal of PSS. Some readily available signals are generator rotor speed, calculated bus frequency, and electrical power. In
Keywords: Stabilizer (aeronautics); Power System Optimization and Stability